Closed loop tracked Doppler optical coherence tomography based heart monitor for the Drosophila melanogaster larvae. Issue 3 (29th April 2015) - Zurauskas, Mantas; Bradu, Adrian; Ferguson, Daniel R.; Hammer, Daniel X.; Podoleanu, Adrian
Abstract : This paper presents a novel instrument for biosciences, useful for studies of moving embryos. A dual sequential imaging/measurement channel is assembled via a closed‐loop tracking architecture. The dual channel system can operate in two regimes: (i) single‐point Doppler signal monitoring or (ii) fast 3‐D swept source OCT imaging. The system is demonstrated for characterizing cardiac dynamics in Drosophila melanogaster larva. Closed loop tracking enables long term in vivo monitoring of the larvae heart without anesthetic or physical restraint. Such an instrument can be used to measure subtle variations in the cardiac behavior otherwise obscured by the larvae movements.A fruit fly larva (top) was continuously tracked for continuous remote monitoring. A heartbeat trace of freely moving larva (bottom) was obtained by a low coherence interferometry based doppler sensing technique. Abstract : This paper presents a new high‐speed closed loop optical tracking tool for biosciences which enables observation of moving embryos. The tracker is applied to monitor the heart dynamics in a freely moving Drosophila larva.